2018
DOI: 10.1136/bcr-2017-223406
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and severe hypokalaemia associated with ectopic ACTH production

Abstract: Ectopic adrenocorticotropic hormone (ACTH) secretion represents 5%-10% of cases of Cushing's syndrome (CS), and approximately 50%-60% of these arise from neuroendocrine lung tumours, including small-cell lung cancer (SCLC). We report a 42-year-old man admitted with hypertension, metabolic alkalosis and severe hypokalaemia. On physical examination, centripetal obesity with 'moon face' and 'buffalo's hump' were identified, and wheezing on left lung was heard. A markedly elevated serum cortisol, ACTH and urine fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Hypokalemia occurred if there was severe hypercortisolism in both CD and ectopic ACTH patients. 4,9,18,[25][26][27][28] Moreover, the UFF/UFE ratio in patients with hypokalemia was significantly higher than that in adrenal CS patients with normokalemia (P < 0.001), suggesting that 11β-HSD2 deficiency was ACTH independent. 29 Otherwise, we analyzed the incidence of hypokalemia in patients hospitalized in our department with ACTH-independent cortisol-secreting adrenal adenoma and carcinoma.…”
Section: Discussionmentioning
confidence: 92%
“…Hypokalemia occurred if there was severe hypercortisolism in both CD and ectopic ACTH patients. 4,9,18,[25][26][27][28] Moreover, the UFF/UFE ratio in patients with hypokalemia was significantly higher than that in adrenal CS patients with normokalemia (P < 0.001), suggesting that 11β-HSD2 deficiency was ACTH independent. 29 Otherwise, we analyzed the incidence of hypokalemia in patients hospitalized in our department with ACTH-independent cortisol-secreting adrenal adenoma and carcinoma.…”
Section: Discussionmentioning
confidence: 92%
“…For example, it has been reported that among seven patients, conventional chemotherapy did not reduce plasma ACTH levels in two patients. Although five patients showed a transient reduction of ACTH levels reduced concomitantly with decreased tumour size and a duration of 1.5–3 months to reach normal ACTH levels, there have been no reports regarding adrenal insufficiency during chemotherapy to the best of our knowledge ( 1 , 4 , 5 , 6 , 7 , 8 ).…”
Section: Discussionmentioning
confidence: 90%
“…EAS represents between 5 and 10% of cases of ACTH-dependent Cushing’s syndrome ( 1 ). EAS results from unregulated ACTH expression by NETs, including SCLC, carcinoid, gut NET, and medullary thyroid carcinoma ( 7 , 8 ). Recently, ICIs have been approved for SCLC, and clinical trials of ICIs for NETs have been performed ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…193 The mechanism of paraneoplastic ACTH-induced hypokalemia is through excessive cortisol secretion by the adrenal gland, which produces a significant mineralocorticoid effect and can be treated with a mineralocorticoid receptor antagonist, such as spironolactone or eplerenone. 217,218 Another cancer-related cause of hypokalemia is through production of lysozyme by various leukemias, resulting in tubular injury and failure to reabsorb urinary potassium. 219,220 The mainstay of treatment involves intravenous or oral potassium, an increase in dietary potassium intake, avoidance of medications known to promote potassium loss (such as diuretics), and co-correction of concurrent hypomagnesemia.…”
Section: Hypokalemiamentioning
confidence: 99%
“…The causes of hypokalemia are grouped into cancer‐related or chemotherapy‐related hypokalemia and can be broadly categorized further into 4 categories: 1) inadequate dietary potassium intake (anorexia, nausea, mucositis, surgery, or tumor‐induced dysphagia/odynophagia), 2) increased extrarenal potassium losses (vomiting and diarrhea from chemotherapy use or gastrointestinal neuroendocrine tumors, 3) increased renal losses (diuretic use, Fanconi syndrome from chemotherapy use [cisplatin, ifosfamide, and lenalidomide], hypomagnesemia [cetuximab use or platinum compounds], or from excess ACTH production by tumor cells [squamous cell cancers, thyroid medullary cancer, neuroendocrine tumors]), and 4) redistribution of potassium into cells (high cell‐turnover states, such as with leukemia, certain lymphomas, and the use of hematopoietic growth factors) 193 . The mechanism of paraneoplastic ACTH‐induced hypokalemia is through excessive cortisol secretion by the adrenal gland, which produces a significant mineralocorticoid effect and can be treated with a mineralocorticoid receptor antagonist, such as spironolactone or eplerenone 217,218 . Another cancer‐related cause of hypokalemia is through production of lysozyme by various leukemias, resulting in tubular injury and failure to reabsorb urinary potassium 219,220 …”
Section: Electrolyte Disorders In Patients With Cancermentioning
confidence: 99%